An Exposition of Transfer Pricing, Fixed Asset Intensity and Capital Intensity on Tax Avoidance - Avriliani Dwi Septiana; Nera Marinda Machdar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In Indonesia, efforts to maximize tax revenue face obstacles, especially related to the difference in interests between the government and the business world. This difference triggers tax avoidance by taxpayers. The researcher made this scientific article, aiming to examine and analyze the influence of transfer pricing, fixed asset intensity and capital intensity on tax avoidance. This study uses a qualitative descriptive method to study a phenomenon by describing the data obtained from literature studies. Literature studies with 39 journals in the 2019-2024 time frame to ensure relevant and up-to-date information and phenomena related to research topics. The results of this study show that the variables of transfer pricing, fixed asset intensity, and capital intensity have an effect on tax avoidance.